Tinjauan Yuridis Terkait Penerapan Persamaan pada Pokoknya untuk Barang dan/atau Jasa Sejenis yang Belum Terdaftar ditinjau dari Undang - Undang Nomor 20 Tahun 2016 Tentang Merek dan Indikasi Geografis - Liza Anggelina Manurung; Rika Ratna Permata; Tasya Safiranita (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Intellectual Property (IP) plays a crucial role in fostering fair business competition. Trademarks as a element of IP serve as distinguishing identifiers that guarantee product quality. In addition, trademarks function as marketing tools in competitive markets and provide protection against bad faith actions by other parties. To obtain legal protection, a trademark must be registered in accordance with statutory requirements. A trademark application may be rejected if these requirements are not fulfilled. A common reason for rejection is the existence of substantial similarity to a previously registered mark or an earlier-filed application for similar goods and/or services. Therefore, clear and consistent standards for determining substantial similarity are essential to ensure legal certainty for applicants.